Identifikasi Ketunaan Anak Berkebutuhan Khusus dengan Algoritma Iterative Dichotomiser 3 (ID3) - Hafidh, Fathul; Kurniawan, Mirza Yogy; Yazidah Anwar, Rezky Izzatul (Jurnal Buana Informatika, 2021)
Abstract. Disability Identification of Children with Special Needs Using An Iterative Dichotomiser 3 Algorithm (ID3). By using the identification of children with special needs, information about children having abnormalities will be collected, and the results are used as the basis for preparing the child's learning program. Identifying disabilities process requires instruments classifying the issues and the disorders. The current disability identification process is extremely complicated, where the average number of instruments made by schools/institutions is 100 pieces. The complexity can also be observed in the presence of similar items as well as some of the same items on different disabilities. The process can be accelerated by doing data mining. One of its models is Iterative Dichotomiser (ID3) that can solve problems by generating a decision tree. This research implemented ID3 model to 152 symptoms as attribute, 11 labels, and 84 data. This model had 91.81% accuracy with cross-validation test. Decision tree generated by this model can make disabilities identification easier. Keywords: Children with Special Needs, Identification, Iterative Dichotomiser (ID3)Abstrak. Dengan adanya Identifikasi Anak Berkebutuhan Khusus akan terhimpun informasi apakah seorang anak mempunyai kelainan kemudian hasilnya dijadikan dasar penyusunan program pembelajaran anak tersebut. Proses identifikasi ketunaan memerlukan instrumen-instrumen dimana dari instrumen tersebut dapat diklasifikasikan sehingga dapat diketahui kecenderungan dari penyimpangan atau kelainan yang dimiliki. Proses identifikasi ketunaan saat ini sangat rumit dimana ratarata jumlah butir instrumen yang dibuat sekolah/lembaga sebanyak 100 buah. Kerumitan juga dapat dilihat dengan adanya butir yang mirip pada ketunaan yang berbeda. Proses ini dapat dipermudah dengan melakukan data mining. Salah satu modelnya adalah Iterative Dichotomiser 3(ID3) yang dapat menyelesaikan masalah dengan menghasilkan pohon keputusan. Dari total instrumen sebanyak 152 Gejala dan data set identifikasi sebanyak 84 ABK, dihasilkan node dari pohon keputusan sebanyak 11 rule. Klasifikasi metode ID3 telah diuji dengan cross-validation dan mendapatkan akurasi sebesar 91.81%. Hasil Pohon keputusan dari metode ID3 memudahkan dalam memprediksi identifikasi ketunaan pada ABK.Kata Kunci: Anak Berkebutuhan Khusus, Identifikasi, Iterative Dichotomiser (ID3)